Prototype Aplikasi Layanan Publik Digital Menggunakan Metode Design Thinking - Bintang Phalosa Wibowo; Bintang Gede Hartono; Rafi Septiawan Nugraha (Router : Jurnal Teknik Informatika dan Terapan, 2026)
The development of information technology drives digital transformation in various sectors, including public services. However, the public still faces various obstacles in accessing public services, such as difficulties in obtaining information, ineffective complaint processes, and a lack of transparency regarding the status of submitted services. This study aims to design a prototype of a digital public service application that can assist the public in accessing service information, submitting complaints, and monitoring report status more effectively. The method used in this study is Design Thinking, which consists of five stages: Empathize, Define, Ideate, Prototype, and Test. Data collection was conducted by distributing questionnaires to 13 respondents from the general public to identify user needs. Based on the requirements analysis, an application prototype named LaporKu was designed, featuring main components such as a dashboard, public complaints, report tracking, public service information, and user profiles. The prototype was then implemented as a website using HTML, CSS, and JavaScript. The prototype testing results showed that the application achieved an overall average score of 4.78, falling into the "Excellent" category. These results indicate that the application is easy to understand, has a clear interface, provides comprehensible information, and is capable of helping users access public services more effectively. Thus, the designed digital public service application prototype is considered a viable solution to support the digitalization of public services and improve accessibility for the community.